Temperature Sensitive Photosynthesis: Point Mutated CEF-G, PRK, or PsbO Act as Temperature-Controlled Switches for Essential Photosynthetic Processes - Bayro-Kaiser, Vinzenz; Nelson, Nathan (Frontiers in Plant Science, 2020)
Temperature sensitive mutants have been widely used to study structure, biogenesis and function of a large variety of essential proteins. However, this method has not yet been exploited for the study of photosynthesis. We used negative selection to isolate temperature-sensitive-photoautotrophic (TSP) mutants in Chlamydomonas reinhardtii. From a population of randomly mutagenized cells (n=12,000), a significant number of TSP mutants (n=157) were isolated. They were able to grow photoautotrophically at 25 °C, but lacked this ability at 37 °C. Further phenotypic characterization of these mutants enabled the identification of three unique and highly interesting mutant strains. Following, the selected strains were genetically characterized by extensive crossing and whole genome sequencing. Correspondingly, the single amino acid changes P628F in the Chloroplast-Elongation-Factor-G (CEF-G), P129L in Phosphoribulokinase (PRK) and P101H in an essential subunit of Photosystem II (PsbO) were identified. These key changes alter the proteins in such way that they were functional at the permissive temperature, however, defective at the restrictive temperature. These mutants are presented here as superb and novel tools for the study of a wide range of aspects relevant to photosynthesis research, tackling three distinct and crucial photosynthetic processes: Chloroplast translation, PET-chain and CBB-cycle.